(untitled) (Journal of Orofacial Research, 1970)
Aim: To evaluate and compare the failure threshold of custom cast post and core using different alloys available in Indian market. Materials and methods: A maxillary typodont central incisor was reduced to a height of 2 mm above CEJ and post space of 10 mm was prepared leaving 4 mm from apex. This was castin stainless steel (SS) and 24 samples were prepared using auto-polymerizing acrylic resin which was divided in four groups of 6 each. Each group was cast using separate alloy. Group 1: Gold alloy, groups 2 and 3: Commonly marketed technique alloys-noble gold dental alloy and kesho alloy and group 4: Base metal alloy. The samples were loaded at 135º using universal testing machine and failure thresholds were recorded and their means were calculated. Statistical analysis used: Analysis of variance and student t-test. Results: The mean values recorded were highest for group D followed by groups A, C and lowest for B. All the groups showed significant differences for the failure threshold tested. Groups B and C showed less failure threshold than the other two groups but much higher than the average masticatory load. Conclusion: Technique alloys can be used as a cheap alternative to the conventional alloys when used for fabrication ofcustom cast posts in terms of failure threshold.